Gestão por competências na avaliação de desempenho organizacional: um estudo de caso na indústria gráfica - Bordignon, Cristina (2019)
In a constantly changing corporate scenario, organizations need to think of strategies not only for competitive and sustainable models, but also for a people management model that meets the aspirations of both, the company itself and the people involved in the organization. The competency management model is based on the tripod, knowledge, skills and attitudes, which seeks to align organizational goals and strategies with competencies, in other worlds, the individual deliverables. Therefore, it is extremely important that the strategies defined through the mapping of competences are aligned with the vision, mission and values of the organization, so that the company can achieve its goals of profit, innovation, market share, among others. Based on this premise, this case study, of qualitative nature, aims to provoke a reflection on how the competency management model interferes in the performance evaluation and, consequently, in the organizational performance in a printing industry in Curitiba, Paraná. The methodology was based on the collection of structured interviews with managers and employees of graphic company, observation and analysis of documents created by the company, in order to gauge the performance of its employees, who work directly with the machine called "lombada quadrada”. The research showed that the graphic company uses the Competence Matrix in its evaluation process in order to identify its employees' technical and behavioral competences, thus choosing productivity indicators, creating its own performance evaluation model. This study demonstrated that the competence assessment, Competency Matrix, proved to be an effective tool for assessing technical competences, leaving gaps in behavioral competencies. Through this analysis, it was possible to verify that the model adopted by the graphic company in has qualities and techniques that can be replicated in other industries, since that the adjustments are made to each type of machine and demand, according to the reality of each company, being it in the graphic industry or other segment.